A method for preparing high temperature corrosion inhibitor

By introducing ferulic acid and silanized phenylatic acid dianhydride into the corrosion inhibitor, a conjugated system and a protective film is formed, the problem of degradation of corrosion inhibition performance of traditional corrosion inhibitors at high temperatures is solved, and efficient metal corrosion protection is achieved.

CN119372655BActive Publication Date: 2025-03-14ZIBO KAIMEIKE IND & TRADE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411930419.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Traditional corrosion inhibitors have deteriorated corrosion inhibition performance at high temperatures, which cannot effectively solve the corrosion problem of cycloalkane acid on normal-depressant distillation devices.

Method used

The imidazoline intermediate is prepared by reacting ferulic acid with diethylene triamine, and further reacting with silanized phenylatic acid dianhydride to produce a corrosion inhibitor. By introducing aromatic ring structures and phenolic hydroxyl groups, a conjugated system and protective film are formed, which improves the high temperature stability and antioxidant ability of the corrosion inhibitor.

Benefits of technology

It significantly improves the corrosion inhibitory properties and oxidation resistance of corrosion inhibitors at high temperatures, can effectively block the contact between corrosion media and metal surfaces, reduce the corrosion rate of metals, and maintain the concentration and activity of their active ingredients during long-term high-temperature operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of petroleum processing, and specifically discloses a method for preparing a high-temperature corrosion inhibitor, the preparation method comprising the following steps: S1: in an inert atmosphere, ferulic acid, diethylenetriamine, a solvent and a catalyst A are mixed evenly, heated to 150-200°C, kept warm for 4-6 hours, cooled, and an imidazoline intermediate is obtained; S2: in an inert atmosphere, pyromellitic anhydride is evenly dispersed in a solvent, and then the imidazoline intermediate and catalyst B are added and mixed evenly, heated to 180-220°C, kept warm for 6-8 hours, cooled, washed, and dried to obtain a corrosion inhibitor; the pyromellitic anhydride is silylated pyromellitic anhydride. The corrosion inhibitor prepared in the present application has good corrosion inhibition performance at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of petroleum processing, and more specifically, to a method for preparing a high-temperature corrosion inhibitor. Background Art

[0002] In recent years, with the deterioration of processed crude oil, the acid value of raw materials often exceeds its design value, which has brought new challenges to crude oil processing. When refining high-acid crude oil, cyclopentane acid corrosion mainly occurs in the high-temperature part of the atmospheric and vacuum distillation unit. Cyclopentane acid corrosion usually occurs in the temperature range of 220~400℃, and the corrosion rate is the highest between 270~280℃. The corrosion rate drops sharply as the temperature continues to rise. The corrosion rate rises sharply at around 350℃. When it exceeds 400℃, cyclopentane acid decomposes and corrosion no longer occurs. Corrosion can cause the wall thickness of the equipment to become thinner and cracks to appear. In severe cases, leakage may even occur, which will not only affect the normal operation of the device and reduce production efficiency, but may also cause safety accidents and threaten personnel and the environment.

[0003] In order to solve the problem of acid corrosion, corrosion inhibitors are usually added to the acidification system. However, most traditional corrosion inhibitors have certain harm to the environment. Imidazoline corrosion inhibitors are non-toxic, have no irritating odor, and are basically harmless to the human body and the surrounding environment. They are environmentally friendly corrosion inhibitors.

[0004] The patent application document with publication number CN116554940A discloses an oily corrosion inhibitor, which includes the following raw materials by weight: 70-90 parts of imidazoline amide corrosion inhibitor, 10-13 parts of auxiliary agent, and 110-130 parts of solvent; the imidazoline amide corrosion inhibitor is prepared by dehydration and cyclization of neodecanoic acid and diethylenetriamine at a molar ratio of 1.1:(1.5-2) at high temperature, and the auxiliary agent includes an amide compound and dialkyl dithiophosphate oxymolybdenum; the amide compound is formed by the reaction of the diethylenetriamine and α-(acetoxy)phenylacetyl chloride.

[0005] In the oily corrosion inhibitor prepared in this patent application document, although the imidazoline amide corrosion inhibitor used is non-toxic and has no irritating odor, the auxiliary agent used has poor temperature resistance. When the temperature is high, the corrosion inhibition performance will decrease. Summary of the invention

[0006] In order to improve the corrosion inhibition performance of the corrosion inhibitor at high temperature, especially to improve the corrosion problem of cyclohexane acid on the atmospheric and vacuum distillation unit at high temperature, the present application provides a preparation method of a high temperature corrosion inhibitor.

[0007] The present application provides a method for preparing a high temperature corrosion inhibitor, which adopts the following technical solution:

[0008] A method for preparing a high temperature corrosion inhibitor comprises the following steps:

[0009] S1: Under an inert atmosphere, ferulic acid, diethylenetriamine, solvent and catalyst A are mixed uniformly, heated to 150-200°C, kept warm for 4-6 hours, and cooled to obtain an imidazoline intermediate;

[0010] S2: Under an inert atmosphere, disperse pyromellitic anhydride evenly in a solvent, then add imidazoline intermediate and catalyst B and mix evenly, heat to 180-220°C, keep warm for 6-8h, cool, wash, and dry to obtain a corrosion inhibitor;

[0011] The molar ratio of ferulic acid, diethylenetriamine and pyromellitic dianhydride is 1:(1.2-1.5):(0.5-1);

[0012] The pyromellitic dianhydride is silylated pyromellitic dianhydride.

[0013] Preferably, the catalyst A is zinc acetate, and the amount of zinc acetate used is 0.03 to 0.05 times the molar number of ferulic acid.

[0014] Preferably, the catalyst B is any one of pyridine and triethylamine, and the amount of catalyst B used is 0.04 to 0.08 times the molar number of pyromellitic dianhydride.

[0015] Preferably, the solvent is N,N-dimethylformamide.

[0016] Preferably, in step S1, the amount of the solvent used is 30% to 40% of the total mass of ferulic acid and diethylenetriamine.

[0017] Preferably, in step S2, the amount of the solvent used is 50% to 70% of the total mass of pyromellitic dianhydride, ferulic acid and diethylenetriamine.

[0018] Beneficial effects: On the one hand, by introducing relatively more aromatic ring structures (ferulic acid, pyromellitic anhydride) into the corrosion inhibitor, a certain conjugated system can be formed inside the molecule. In a high-temperature environment, the heat absorbed by the corrosion inhibitor molecule can be quickly transferred and dispersed through the conjugated system of the aromatic ring, reducing the possibility of chemical bond breakage caused by local energy accumulation, thereby maintaining the stability of the molecular structure and enabling it to withstand higher temperatures. On the other hand, by introducing phenolic hydroxyl groups (ferulic acid) into the corrosion inhibitor, the phenolic hydroxyl groups can react with free radicals in the environment, thereby interrupting the propagation of the oxidation chain reaction; at the same time, functional groups such as carbonyl groups in the molecule may also participate in some redox processes and consume oxidizing substances in the system. In addition, the presence of multiple conjugated aromatic ring structures in the molecule and the electronic interactions between various functional groups produce a certain electron delocalization effect, which also helps to improve the antioxidant capacity of the corrosion inhibitor.

[0019] Preferably, the method for preparing the silylated pyromellitic dianhydride comprises the following steps:

[0020] Dissolve pyromellitic dianhydride in an organic solvent, then add a silane coupling agent, heat to 105-115°C, keep warm for 4.5-5h, cool, extract, purify, wash, and dry to obtain silylated pyromellitic dianhydride.

[0021] Preferably, the molar ratio of the pyromellitic anhydride to the silane coupling agent is (1-1.5):0.8.

[0022] Beneficial effects: On the one hand, the molecular structure of silylated pyromellitic anhydride has enhanced temperature resistance and can effectively resist the attack of moisture under high temperature conditions, thereby ensuring the integrity of the molecular structure of the corrosion inhibitor, so that the corrosion inhibitor prepared later can maintain the concentration and activity of its effective ingredients in the equipment during long-term high-temperature operation, and continue to play a protective role on the metal surface of the equipment, reducing the risk of metal corrosion caused by the failure of the corrosion inhibitor hydrolysis. On the other hand, giving the corrosion inhibitor a certain hydrophobic property is conducive to the formation of a hydrophobic protective film on the metal surface. The acidic substances in crude oil and the alkaline impurities that may exist mostly reach the metal surface with the flow of water. Due to the hydrophobicity of the corrosion inhibitor protective film, these waters dissolved with acidic or alkaline substances are effectively blocked outside the film, greatly reducing the chance of contact between the metal surface and corrosive substances, thereby reducing the possibility of corrosion at the source.

[0023] In addition, when the protective film is combined with the metal surface, silylated pyromellitic dianhydride can undergo certain chemical bonding or strong adsorption with the metal surface, making the protective film more firmly attached to the metal surface and improving the effect of the corrosion inhibitor in inhibiting metal corrosion.

[0024] Preferably, the organic solvent comprises acetone and a water absorbent, and the mass fraction of the water absorbent in the acetone is 10% to 15%.

[0025] Preferably, the water absorbent is a magnetic 3A molecular sieve.

[0026] Beneficial effects: The addition of magnetic 3A molecular sieve greatly reduces the water content of the system by absorbing water, minimizes the decomposition of pyromellitic anhydride, and can also create a relatively stable and dry environment locally, making the chemical environment of pyromellitic anhydride more stable and the molecular structure less likely to be destroyed, which helps maintain its reaction activity and promotes the synthesis efficiency and purity of the corrosion inhibitor. In the subsequent product processing process, only an external magnetic field needs to be applied, and the magnetic 3A molecular sieve will be adsorbed and aggregated under the action of the magnetic field force, thereby quickly separating from the corrosion inhibitor and other substances in the reaction system, without the need for complex separation processes and cumbersome operating steps.

[0027] Preferably, in step S2, after adding the imidazoline intermediate, a dispersant is added in an amount of 0.05 to 0.2 times the total molar number of ferulic acid, diethylenetriamine and pyromellitic dianhydride.

[0028] Preferably, the dispersant is polyethylene glycol 600.

[0029] Beneficial effects: Polyethylene glycol 600 utilizes the hydrogen bonding between its molecular chain and the reactant molecules and the steric hindrance effect generated by itself to keep the reactants in a uniformly dispersed state, which is conducive to the smooth progress of the reaction.

[0030] Preferably, in step S1, polyaspartic acid is added after ferulic acid, and the molar ratio of polyaspartic acid to ferulic acid is (0.1-0.4):1.

[0031] Beneficial effects: The imidazoline intermediate synthesized by polyaspartic acid, ferulic acid and diethylenetriamine has not only an imidazole ring, but also incorporates multiple functional groups such as the carboxyl group and amide bond of polyaspartic acid and the phenolic hydroxyl group of ferulic acid, forming a macromolecule with a certain spatial structure. This complex molecular chain structure can form a more multi-layered protective film on the metal surface, which can not only effectively block the contact between the corrosive medium and the metal surface, but also play a corrosion inhibition role under different corrosive environments through the action of different functional groups. In addition, the introduction of polyaspartic acid gives the corrosion inhibitor a certain flexibility, which enables it to stretch and bend freely on the metal surface, better adapt to the microscopic unevenness of the metal surface, and thus achieve comprehensive coverage.

[0032] Preferably, an antioxidant is added to the solvent in both step S1 and step S2, and the mass fraction of the antioxidant in the solvent is 0.5% to 1%.

[0033] Preferably, the antioxidant is antioxidant 1010.

[0034] Preferably, the corrosion inhibitor prepared in step S2 is further compounded with molybdate, and the compounding method comprises the following steps:

[0035] Dissolve the corrosion inhibitor in ethylene glycol, then add ammonium molybdate and glucose and mix evenly, adjust the pH to 5-6, heat to 90-110°C, keep warm for 2-4 hours, cool down, separate the solid and liquid, distill, and dry to obtain;

[0036] The mass ratio of the corrosion inhibitor to ammonium molybdate is 1:(0.1-0.3), and the mass ratio of ammonium molybdate to glucose is 1:(1.1-1.3).

[0037] Beneficial effects: The active groups of the corrosion inhibitor itself have a certain adsorption effect on the metal surface. The addition of ammonium molybdate further enhances this adsorption through chemical bonding and coordination, and the hydrogen bond network constructed by glucose makes the protective film denser, effectively blocking the contact between moisture, acidic substances, alkaline substances and corrosive ions and the metal surface, thereby significantly reducing the corrosion rate of the metal.

[0038] Preferably, the corrosion inhibitor prepared in step S2 is further compounded with molybdate, and the compounding method comprises the following steps:

[0039] Dissolve the corrosion inhibitor in ethylene glycol, add cetyl alcohol and mix evenly, then add ammonium molybdate and glucose and mix evenly, adjust the pH to 5-6, heat to 90-110℃, keep warm for 3-5h, cool, separate solid and liquid, distill, and dry to obtain;

[0040] The mass ratio of the corrosion inhibitor to ammonium molybdate is 1:(0.1-0.3), the mass ratio of ammonium molybdate to glucose is 1:(1.1-1.3), and the dosage of cetyl alcohol is 0.05-0.15 times the mass of the corrosion inhibitor.

[0041] Beneficial effects: The active groups of the corrosion inhibitor itself have good adsorption on the metal surface, and the addition of ammonium molybdate further enhances this adsorption through chemical bonding and coordination. The introduction of cetyl alcohol improves the dispersibility and wettability of the corrosion inhibitor, allowing the corrosion inhibitor to cover the metal surface more evenly, forming a denser and more stable protective film.

[0042] The hydrogen bond network constructed by glucose and the interlaced structure of cetyl alcohol work together to make the protective film denser, effectively blocking the contact between water, acidic substances, alkaline substances and corrosive ions and the metal surface. At the same time, the thickening effect of cetyl alcohol also enhances the mechanical strength and stability of the protective film, enabling it to better resist the impact of factors such as erosion, corrosion and temperature changes of corrosive media during long-term use.

[0043] The compounded corrosion inhibitor can form a more uniform, dense and stable protective film on the metal surface, thereby more effectively blocking the contact between the corrosive medium and the metal surface and significantly reducing the corrosion rate of the metal.

[0044] In summary, this application has the following beneficial effects:

[0045] 1. The present application uses ferulic acid and diethylenetriamine to react to prepare an imidazoline intermediate, which is then further reacted with silylated pyromellitic anhydride to prepare a corrosion inhibitor. The imidazole ring interacts with the aromatic ring and the silane structure to form a corrosion inhibitor molecule with a conjugated structure, while retaining the functionality of the phenolic hydroxyl group. Not only can a dense protective film be formed on the metal surface, effectively blocking the contact between the corrosive medium and the metal surface, and having a high corrosion inhibition rate, but the corrosion inhibitor can also maintain stable chemical properties and strong antioxidant properties at high temperatures.

[0046] 2. In the step of synthesizing the corrosion inhibitor, a certain amount of polyaspartic acid is compounded when preparing the imidazoline intermediate. After the long chain structure of polyaspartic acid reacts with ferulic acid and diethylenetriamine, the molecular chain of the imidazoline intermediate will grow and increase in branches, which will help the corrosion inhibitor to form a denser and more continuous protective film on the metal surface. The long chain structure can be intertwined and entangled with each other, covering the metal surface to form a physical barrier to block the penetration of corrosive media. In addition, polyaspartic acid can form a complex with metal ions (such as iron ions, etc.) to reduce the dissolution rate of metal ions. The imidazoline structure formed by the reaction of ferulic acid and diethylenetriamine can adjust the charge distribution on the metal surface. The three work together to reduce the activity of the anode reaction and slow down the corrosion of the metal.

[0047] 3. In the step of synthesizing the corrosion inhibitor, the present application also adds polyethylene glycol 600, which can promote the uniform dispersion of the reactants and adjust the viscosity of the reaction system, so that the reaction is more sufficient and uniform, thereby improving the reaction efficiency. In addition, polyethylene glycol 600 may affect the structure and distribution of the corrosion inhibitor molecules, so that the corrosion inhibitor can better form a continuous and dense protective film on the metal surface, thereby improving the corrosion inhibition effect. DETAILED DESCRIPTION

[0048] The present application is further described in detail below in conjunction with embodiments and preparation examples.

[0049] Ferulic acid, chemical name 3-methoxy-4-hydroxycinnamic acid, 98%, was purchased from Hebei Hongtao Bioengineering Co., Ltd.;

[0050] Pyromellitic anhydride, purity 99.5%, purchased from Jiangsu Hualun Chemical Co., Ltd.;

[0051] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0052] Preparation Examples 1-3 Silylated Pyromellitic Dianhydride

[0053] Preparation Example 1

[0054] Select a three-necked flask with a stirrer, a condenser and a thermometer, add 240 ml of dried acetone, then add 1 mol of dried pyromellitic anhydride, heat to 45°C, and stir at a speed of 200 r / min to completely dissolve pyromellitic anhydride, slowly drop 0.8 mol of γ-aminopropyltriethoxysilane, keep the stirring speed unchanged during the dropwise addition, and control the dropwise addition time to 40 min. After the dropwise addition is completed, heat to 105°C and keep warm for 5 h, during which the stirring speed is kept constant. The reaction mixture remained unchanged. After the reaction was completed, the mixture was cooled to room temperature, 60 ml of deionized water was added, the mixture was allowed to stand for 60 min, and the extraction was repeated three times. The organic phase obtained by separation was subjected to reduced pressure distillation at a temperature of 80 ° C and a pressure of 0.08 MPa to remove the acetone solvent to obtain a crude product. The crude product was then recrystallized using 120 ml of anhydrous ethanol. The crystallized product was filtered, washed three times with anhydrous ethanol at zero degrees Celsius, and dried at 80 ° C under a nitrogen atmosphere for 6 hours to obtain silylated isophthalic acid dianhydride.

[0055] Preparation Example 2

[0056] Select a three-necked flask with a stirrer, a condenser and a thermometer, add 350 ml of dried acetone, then add 1.5 mol of dried pyromellitic anhydride, heat to 50 ° C, and stir at a speed of 200 r / min to completely dissolve pyromellitic anhydride, slowly add 0.8 mol of γ-aminopropyltriethoxysilane, keep the stirring speed unchanged during the addition, and control the addition time to 45 min. After the addition is completed, heat to 115 ° C and keep warm for 4.5 h. During this period, adjust the stirring speed to 3 00r / min, after the reaction is completed, cool to room temperature, add 70ml of deionized water, let stand for 60min, extract in layers, repeat three times, and distill the organic phase obtained by separation under reduced pressure at 80℃ and 0.08MPa to remove the acetone solvent to obtain a crude product, which is then recrystallized with 130ml of anhydrous ethanol. The crystallized product is filtered, washed with anhydrous ethanol at zero degrees Celsius for 3 times, and dried at 80℃ under a nitrogen atmosphere for 10h to obtain silylated isophthalic acid dianhydride.

[0057] Preparation Example 3

[0058] Select a three-necked flask with a stirrer, a condenser and a thermometer, add 300 ml of dried acetone, then add 1.3 mol of dried pyromellitic anhydride, heat to 50 ° C, and stir at a speed of 200 r / min to completely dissolve pyromellitic anhydride, slowly add 0.8 mol of γ-aminopropyltriethoxysilane, keep the stirring speed unchanged during the addition, and control the addition time to 40 min. After the addition is completed, heat to 110 ° C and keep warm for 5 h. During this period, adjust the stirring speed to 30 0r / min, after the reaction is completed, cool to room temperature, add 65ml of deionized water, let stand for 60min, extract in layers, repeat three times, and distill the organic phase obtained by separation under reduced pressure at 80℃ and 0.08MPa to remove the acetone solvent to obtain a crude product, which is then recrystallized with 125ml of anhydrous ethanol. The crystallized product is filtered, washed with zero-degree Celsius anhydrous ethanol for 3 times, and dried at 80℃ under a nitrogen atmosphere for 8h to obtain silylated isophthalic acid dianhydride.

[0059] Example 1

[0060] This embodiment provides a method for preparing a high temperature corrosion inhibitor, comprising the following steps:

[0061] S1: 1 mol of ferulic acid, 1.2 mol of diethylenetriamine, 100 g of N,N-dimethylformamide and 0.03 mol of zinc acetate were added to a four-necked flask equipped with a water separator and a nitrogen inlet, and nitrogen was introduced to exhaust the air, and then stirred and mixed for 30 min at a speed of 300 r / min. The temperature was first raised to 150°C and kept warm for 30 min. The water separator separated the generated water in time, and then the temperature was raised to 180°C, stirred continuously, kept warm for 6 h, and cooled to room temperature to obtain an imidazoline intermediate;

[0062] S2: Under the protection of a continuous nitrogen atmosphere, 0.5 mol of pyromellitic anhydride was slowly added to 215 g of N, N-dimethylformamide, stirring was started at 800 r / min, and the mixture was stirred and dispersed for 30 min. The imidazoline intermediate was slowly added dropwise at a speed of 600 r / min. After the addition was complete, the mixture was stirred and mixed for 15 min. Then 0.02 mol of pyridine was slowly added dropwise while stirring at a speed of 200 r / min. After the addition was complete, the temperature was slowly raised to 180°C, kept warm for 8 h, and naturally cooled to room temperature. Three times the mass of the product was added in n-heptane to dilute and dissolve the mixture, and the mixture was washed three times with an equal volume of deionized water. The n-heptane was removed by reduced pressure distillation at a temperature of 80°C and a vacuum degree of 0.1 MPa. The mixture was then transferred to a vacuum drying oven and dried at 50°C for 3 h to obtain a corrosion inhibitor.

[0063] Wherein, pyromellitic acid dianhydride is silylated pyromellitic acid dianhydride from Preparation Example 1 (50% of the mass of silylated pyromellitic acid dianhydride in Preparation Example 1).

[0064] Example 2

[0065] This embodiment provides a method for preparing a high temperature corrosion inhibitor, comprising the following steps:

[0066] S1: 1 mol of ferulic acid, 1.5 mol of diethylenetriamine, 140 g of N,N-dimethylformamide and 0.05 mol of zinc acetate were added to a four-necked flask equipped with a water separator and a nitrogen inlet, and nitrogen was introduced to exhaust the air, and then stirred and mixed for 30 min at a speed of 300 r / min. The temperature was first raised to 150°C and kept warm for 30 min. The water separator separated the generated water in time, and then the temperature was raised to 200°C, stirred continuously, kept warm for 4 h, and cooled to room temperature to obtain an imidazoline intermediate;

[0067] S2: Under the protection of a continuous nitrogen atmosphere, 1 mol of pyromellitic anhydride was slowly added to 400 g of N, N-dimethylformamide, stirring was started at a speed of 800 r / min, and the mixture was stirred and dispersed for 30 min. The imidazoline intermediate was slowly added dropwise at a speed of 600 r / min. After the addition was complete, the mixture was stirred and mixed for 15 min. Then 0.08 mol of pyridine was slowly added dropwise while stirring at a speed of 200 r / min. After the addition was complete, the temperature was slowly raised to 220°C, kept warm for 6 h, and naturally cooled to room temperature. Three times the mass of the product was added in n-heptane to dilute and dissolve the mixture, and the mixture was washed three times with an equal volume of deionized water. The n-heptane was removed by reduced pressure distillation at a temperature of 80°C and a vacuum degree of 0.1 MPa. The mixture was then transferred to a vacuum drying oven and dried at 50°C for 3 h to obtain a corrosion inhibitor.

[0068] Wherein, pyromellitic acid dianhydride is silylated pyromellitic acid dianhydride from Preparation Example 2 (taking 67% of the mass of silylated pyromellitic acid dianhydride in Preparation Example 2).

[0069] Example 3

[0070] This embodiment provides a method for preparing a high temperature corrosion inhibitor, comprising the following steps:

[0071] S1: 1 mol of ferulic acid, 1.3 mol of diethylenetriamine, 120 g of N,N-dimethylformamide and 0.04 mol of zinc acetate were added to a four-necked flask equipped with a water separator and a nitrogen inlet, and nitrogen was introduced to exhaust the air, and then stirred and mixed for 30 min at a speed of 300 r / min. The temperature was first raised to 150°C and kept warm for 30 min. The water separator separated the generated water in time, and then the temperature was raised to 190°C, stirred continuously, kept warm for 5 h, and cooled to room temperature to obtain an imidazoline intermediate;

[0072] S2: Under the protection of a continuous nitrogen atmosphere, 0.7 mol of pyromellitic anhydride was slowly added to 400 g of N, N-dimethylformamide, stirring was started at 800 r / min, and the mixture was stirred and dispersed for 30 min. The imidazoline intermediate was slowly added dropwise at a speed of 600 r / min. After the addition was complete, the mixture was stirred and mixed for 15 min. Then 0.05 mol of pyridine was slowly added dropwise while stirring at a speed of 200 r / min. After the addition was complete, the temperature was slowly raised to 200°C, and the mixture was kept warm for 7 h. The mixture was naturally cooled to room temperature, and 3 times the mass of the product was added in n-heptane to dilute and dissolve the mixture. The mixture was washed 3 times with an equal volume of deionized water, and the n-heptane was removed by reduced pressure distillation at a temperature of 80°C and a vacuum degree of 0.1 MPa. The mixture was then transferred to a vacuum drying oven and dried at 50°C for 3 h to obtain a corrosion inhibitor.

[0073] Wherein, pyromellitic acid dianhydride is silylated pyromellitic acid dianhydride from Preparation Example 3 (54% of the mass of silylated pyromellitic acid dianhydride in Preparation Example 3).

[0074] Example 4

[0075] The difference between this embodiment and embodiment 3 is that:

[0076] S2: Under the protection of a continuous nitrogen atmosphere, 0.7 mol of pyromellitic anhydride was slowly added to 400 g of N, N-dimethylformamide, stirring was started at a speed of 800 r / min, and the mixture was stirred and dispersed for 30 min. The imidazoline intermediate was slowly added dropwise at a speed of 600 r / min. After the addition was complete, 0.15 mol of polyethylene glycol 600 was slowly added, and the mixture was stirred and mixed for 15 min. Then 0.05 mol of pyridine was slowly added dropwise while stirring at a speed of 200 r / min. After the addition was complete, the temperature was slowly raised to 200°C, and the mixture was kept warm for 7 h. The mixture was naturally cooled to room temperature, and 3 times the mass of n-heptane of the product was added to dilute and dissolve the mixture. The mixture was washed 3 times with an equal volume of deionized water, and the n-heptane was removed by reduced pressure distillation at a temperature of 80°C and a vacuum degree of 0.1 MPa. The mixture was then transferred to a vacuum drying oven and dried at 50°C for 3 h to obtain a corrosion inhibitor.

[0077] The rest is the same as in Example 3.

[0078] Example 5

[0079] This embodiment provides a method for preparing a high temperature corrosion inhibitor, comprising the following steps:

[0080] S1: 1 mol of ferulic acid, 0.1 mol of polyaspartic acid, 1.3 mol of diethylenetriamine, 120 g of N,N-dimethylformamide and 0.04 mol of zinc acetate were added to a four-necked flask equipped with a water separator and a nitrogen inlet, and nitrogen was introduced to exhaust the air, and then stirred and mixed for 30 min at a speed of 300 r / min. The temperature was first raised to 150°C and kept warm for 30 min. The water separator separated the generated water in time, and then the temperature was raised to 190°C, and the mixture was kept stirred for 5 h, and then cooled to room temperature to obtain an imidazoline intermediate;

[0081] S2: Under the protection of a continuous nitrogen atmosphere, 0.8 mol of pyromellitic anhydride was slowly added to 400 g of N, N-dimethylformamide, stirring was started at a speed of 800 r / min, and the mixture was stirred and dispersed for 30 min. The imidazoline intermediate was slowly added dropwise at a speed of 600 r / min. After the addition was complete, 0.3 mol of polyethylene glycol 600 was slowly added, and the mixture was stirred and mixed for 15 min. Then 0.05 mol of pyridine was slowly added dropwise while stirring at a speed of 200 r / min. After the addition was complete, the temperature was slowly raised to 200°C, and the mixture was kept warm for 7 h. The mixture was naturally cooled to room temperature, and 3 times the mass of the product was added in n-heptane to dilute and dissolve the mixture. The mixture was washed 3 times with an equal volume of deionized water, and the n-heptane was removed by reduced pressure distillation at a temperature of 80°C and a vacuum degree of 0.1 MPa. The mixture was then transferred to a vacuum drying oven and dried at 50°C for 3 h to obtain a corrosion inhibitor.

[0082] Wherein, pyromellitic acid dianhydride is silylated pyromellitic acid dianhydride from Preparation Example 3 (taking 61% of the mass of silylated pyromellitic acid dianhydride in Preparation Example 3).

[0083] Example 6

[0084] The difference between this embodiment and embodiment 5 is that:

[0085] In step S1, the amount of polyaspartic acid used is 0.4 mol; in step S2, the amount of polyethylene glycol 600 used is 0.6 mol;

[0086] The N,N-dimethylformamide in step S1 and step S2 both contain 0.5% by mass of antioxidant 1010.

[0087] The rest is the same as Example 5.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 6 is that:

[0090] In step S1, the amount of polyaspartic acid used is 0.3 mol; in step S2, the amount of polyethylene glycol 600 used is 0.5 mol;

[0091] The N,N-dimethylformamide in step S1 and step S2 both contain 1% by mass of antioxidant 1010.

[0092] The rest is the same as Example 6.

[0093] Comparative Example 1

[0094] The difference between this comparative example and Example 1 is:

[0095] Pyromellitic anhydride is not silylated.

[0096] The rest is the same as in Example 1.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is:

[0099] An equimolar amount of oleic acid was used to replace ferulic acid.

[0100] The rest is the same as in Example 1.

[0101] Performance Testing

[0102] Test materials and steps: A refinery's three-line distillate oil, with an acid value of 3.39 mgKOH / g, was added with 2% by mass of cyclohexane acid with an acid value of 200 mgKOH / g to prepare the test standard oil (acid value of 20 mgKOH / g), which was added into a 1L high-temperature and high-pressure reactor. For each group of tests, 3 A3 carbon steel sheets (50×10×3mm) were hung in the high-temperature and high-pressure reactor, high-purity nitrogen was introduced to displace the oxygen in the high-temperature and high-pressure reactor, and then the high-temperature and high-pressure reactor was sealed.

[0103] Test temperature: 350±5℃

[0104] Test time: 96h

[0105] Evaluation method: After the test, cool to room temperature, take out the carbon steel sheet, and weigh it accurately after processing according to the standard ASTM G1-2003 steps, and take the average value; the blank control operation steps are the same as above, except that no corrosion inhibitor is added during the test.

[0106] (1) Phase 1 testing

[0107] Experimental corrosion inhibitor: Example 1 and blank control group

[0108] Corrosion inhibitor dosage: 5mg / kg, 15mg / kg, 25mg / kg.

[0109] Test results: see Table 1

[0110] Table 1 Corrosion inhibition rate of the corrosion inhibitor in Example 1 and performance test data of the blank control group

[0111]

[0112] (2) Second stage testing

[0113] Experimental corrosion inhibitor: Examples 2 to 7 and Comparative Examples 1 to 2

[0114] Corrosion inhibitor dosage: 15mg / kg

[0115] Test results: see Table 2

[0116] Table 2 Corrosion inhibition performance test data of the corrosion inhibitors of Examples 2 to 7 and Comparative Examples 1 to 2

[0117]

[0118] (3) Second stage testing

[0119] Corrosion inhibitor for test: Sample 1~Sample 4

[0120] Corrosion inhibitor dosage: 20mg / kg

[0121] Test results: see Table 3

[0122] The preparation method of sample 1 includes the following steps:

[0123] Take 10 g of the corrosion inhibitor prepared in Example 7 and add it to 200 ml of anhydrous ethylene glycol, stir until it is evenly dispersed, then add 1 g of ammonium molybdate and 1.1 g of glucose, stir and mix evenly, use 5% by mass dilute sulfuric acid to adjust the pH to 5, heat to 90°C, keep warm for 4 hours, cool to room temperature, filter, distill until no water is analyzed, and then transfer to a drying oven at 50°C and dry for 2 hours to obtain sample 1.

[0124] The preparation method of sample 2 includes the following steps:

[0125] Take 10 g of the corrosion inhibitor prepared in Example 7 and add it to 200 ml of anhydrous ethylene glycol, stir until it is evenly dispersed, then add 3 g of ammonium molybdate and 4 g of glucose, stir and mix evenly, use 5% by mass dilute sulfuric acid to adjust the pH to 6, heat to 110°C, keep warm for 2 hours, cool to room temperature, filter, distill until no water is analyzed, and then transfer to a drying oven and dry at 50°C for 2 hours to obtain sample 2.

[0126] The preparation method of sample 3 includes the following steps:

[0127] Take 10 g of the corrosion inhibitor prepared in Example 7 and add it to 200 ml of anhydrous ethylene glycol, stir until it is evenly dispersed, then add 1 g of ammonium molybdate, 1.1 g of glucose and 0.5 g of cetyl alcohol, stir and mix evenly, use 5% by mass dilute sulfuric acid to adjust the pH to 5, heat to 90°C, keep warm for 5 hours, cool to room temperature, filter, distill until no water is precipitated, then transfer to a drying oven, dry at 50°C for 2 hours, and obtain sample 3.

[0128] The preparation method of sample 4 includes the following steps:

[0129] Take 10 g of the corrosion inhibitor prepared in Example 7 and add it to 200 ml of anhydrous ethylene glycol, stir until it is evenly dispersed, then add 3 g of ammonium molybdate, 4 g of glucose and 1.5 g of cetyl alcohol, stir and mix evenly, use 5% by mass dilute sulfuric acid to adjust the pH to 5, heat to 110°C, keep warm for 3 hours, cool to room temperature, filter, distill until no water is precipitated, then transfer to a drying oven, dry at 50°C for 2 hours, and obtain sample 4.

[0130] Table 3 Corrosion inhibition performance test data of sample 1 to sample 4

[0131]

[0132] By comparing and analyzing the performance test data in Table 1 to Table 3, we can see that:

[0133] By increasing the dosage of corrosion inhibitor, the corrosion inhibition performance is gradually improved. When the dosage of corrosion inhibitor increases to a certain level, the improvement of corrosion inhibition performance will gradually decrease. Combined with cost analysis, the recommended dosage of corrosion inhibitor is 15 mg / kg.

[0134] By comparing and analyzing Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the corrosion inhibitor has good corrosion inhibition performance at high temperatures by using ferulic acid and silylated pyromellitic acid dianhydride. This is mainly because the corrosion inhibitor prepared by using ferulic acid and silylated pyromellitic acid dianhydride can provide good corrosion inhibition performance at high temperatures through more stable chemical bonding, better thermal stability, denser protective film and stronger hydrophobicity.

[0135] Under high temperature conditions, the corrosion inhibitors prepared in Examples 1 to 3 all exhibited good corrosion inhibition performance, which indicates that by optimizing the distribution ratio of each component, the adverse effect of high temperature on the corrosion inhibitor has been successfully overcome, so that the corrosion inhibitor can stably protect the metal from corrosion in a high temperature environment.

[0136] Comparative analysis of Examples 3 to 7 shows that the corrosion inhibition performance is improved by compounding polyethylene glycol 600 and polyaspartic acid. This is mainly because polyethylene glycol 600 and polyaspartic acid help the corrosion inhibitor to form a denser and more continuous protective film on the metal surface, reducing the corrosion rate of the metal in the corresponding corrosive environment, thereby showing a better corrosion inhibition effect.

[0137] Comparative analysis of samples 1 to 4 shows that by compounding the corrosion inhibitor prepared in Example 7 with ammonium molybdate, glucose, and cetyl alcohol, the corrosion inhibition performance is further improved. This is mainly due to the fact that the active groups of the corrosion inhibitor itself have a good adsorption effect on the metal surface, and the addition of ammonium molybdate further enhances this adsorption through chemical bonding and coordination. The introduction of cetyl alcohol improves the dispersibility and wettability of the corrosion inhibitor, allowing the corrosion inhibitor to be more evenly covered on the metal surface to form a denser and more stable protective film. The hydrogen bond network constructed by glucose and the interlaced structure of cetyl alcohol work together to make the protective film denser, effectively blocking the contact between moisture, acidic substances, alkaline substances and corrosive ions and the metal surface.

[0138] In addition, when the temperature rises, glucose may decompose, but its decomposition products may form a carbonaceous protective film on the metal surface, which can to a certain extent prevent the contact between the corrosive medium and the metal at high temperature, while cetyl alcohol may form a structure similar to a "buffer layer" between the metal surface and the corrosion inhibitor at high temperature. Its long chain can be intertwined with the corrosion inhibitor molecules. When the temperature rises, cetyl alcohol can help other corrosion inhibition components to better adhere to the metal surface and reduce the situation where the corrosion inhibitor is separated from the metal surface due to high temperature. At the same time, cetyl alcohol may also interact with the decomposition products of glucose to enhance the continuity and stability of the carbonaceous protective film, and together with the passivation film of ammonium molybdate, it forms a more effective multi-layer protection system, further improving the high temperature resistance of the entire corrosion inhibitor formula.

Claims

1. A method for preparing a high temperature corrosion inhibitor, characterized in that: The steps include: S1: Under an inert atmosphere, ferulic acid, diethylenetriamine, solvent and catalyst A are mixed uniformly, heated to 150-200°C, kept warm for 4-6 hours, and cooled to obtain an imidazoline intermediate; S2: Under an inert atmosphere, pyromellitic anhydride is uniformly dispersed in a solvent, and then the imidazoline intermediate and catalyst B are added and mixed uniformly, and the temperature is raised to 180-220°C, and the temperature is kept for 6-8 hours, and the temperature is lowered, and the mixture is diluted with n-heptane, washed, and dried to obtain a corrosion inhibitor; The molar ratio of ferulic acid, diethylenetriamine and pyromellitic dianhydride is 1:(1.2-1.5):(0.5-1); The catalyst A is zinc acetate, and the amount of zinc acetate is 0.03 to 0.05 times the molar number of ferulic acid; The catalyst B is any one of pyridine and triethylamine, and the amount of the catalyst B is 0.04 to 0.08 times the molar number of pyromellitic anhydride; The solvent is N,N-dimethylformamide; The silylated pyromellitic dianhydride is silylated pyromellitic dianhydride, and the preparation method of the silylated pyromellitic dianhydride comprises the following steps: Dissolve pyromellitic anhydride in an organic solvent, then add a silane coupling agent, heat to 105-115°C, keep warm for 4.5-5h, cool, extract, purify, wash, and dry to obtain silylated pyromellitic anhydride; the molar ratio of pyromellitic anhydride to the silane coupling agent is (1-1.5):0.8; The organic solvent includes acetone and a water absorbent, and the mass fraction of the water absorbent in the acetone is 10% to 15%.

2. The method for preparing a high temperature corrosion inhibitor according to claim 1, characterized in that: In step S2, after adding the imidazoline intermediate, a dispersant is added in an amount of 0.05 to 0.2 times the total molar number of ferulic acid, diethylenetriamine and pyromellitic dianhydride.

3. The method for preparing a high temperature corrosion inhibitor according to claim 2, characterized in that: The dispersant is polyethylene glycol 600.

4. The method for preparing a high temperature corrosion inhibitor according to claim 1, characterized in that: In step S1, polyaspartic acid is added after ferulic acid, and the molar ratio of polyaspartic acid to ferulic acid is (0.1-0.4):

1.

5. The method for preparing a high temperature corrosion inhibitor according to claim 4, characterized in that: Antioxidants are added to the solvents in both step S1 and step S2, and the mass fraction of the antioxidant in the solvent is 0.5% to 1%.

6. The method for preparing a high temperature corrosion inhibitor according to claim 1, characterized in that: The corrosion inhibitor prepared in step S2 is further compounded with molybdate, and the compounding method comprises the following steps: Dissolve the corrosion inhibitor in ethylene glycol, then add ammonium molybdate and glucose and mix evenly, adjust the pH to 5-6, heat to 90-110°C, keep warm for 2-4 hours, cool down, separate the solid and liquid, distill, and dry to obtain; The mass ratio of the corrosion inhibitor to ammonium molybdate is 1:(0.1-0.3), and the mass ratio of ammonium molybdate to glucose is 1:(1.1-1.3).

7. The method for preparing a high temperature corrosion inhibitor according to claim 1, characterized in that: The corrosion inhibitor prepared in step S2 is further compounded with molybdate, and the compounding method comprises the following steps: Dissolve the corrosion inhibitor in ethylene glycol, add cetyl alcohol and mix evenly, then add ammonium molybdate and glucose and mix evenly, adjust the pH to 5-6, heat to 90-110℃, keep warm for 3-5h, cool, separate solid and liquid, distill, and dry to obtain; The mass ratio of the corrosion inhibitor to ammonium molybdate is 1:(0.1-0.3), the mass ratio of ammonium molybdate to glucose is 1:(1.1-1.3), and the dosage of cetyl alcohol is 0.05-0.15 times the mass of the corrosion inhibitor.

Citation Information

Patent Citations

  • Oily corrosion inhibitor and preparation method thereof

    CN116554940A

  • Imidazoline high-temperature-resistant corrosion inhibitor and preparation method thereof

    CN110042398A

  • Composite imidazoline corrosion inhibitor for oil transportation station and preparation method of composite imidazoline corrosion inhibitor

    CN113667983A